The Influence of Cake Learning Application on Students' Speaking Ability - Wahyuni, Kiki; Fitri, Mainar (Indonesian Journal of Integrated English Language Teaching, 2023)
The purpose of this research was to find out whether there is a significant influence between students' speaking ability before and after being taught by using the cake learning application. This research was quantitative. The design of this research was a pre-experimental method with one group pre-test design and post-test design. The research used one class as the sample of the research by using a convenience sampling technique which the total of sample were 33 students. To collect data, the researcher used a test to determine students' speaking ability. In analyzing the data, the researcher used a paired t test by using SPSS version 25. The results of data analyzed showed that the mean score of students after being taught by using the Cake Learning Application (78.24) was higher than before being taught by using the Cake Learning Application (57.64). It can be concluded that there was an influence between students' speaking ability before and after being taught by using the cake learning application. Keywords: Cake Learning Application, speaking